Extension of charge-state-distribution calculations for ion-solid collisions towards low velocities and many-electron ions - Lamour, E. (2015)
Knowledge of the detailed evolution of the whole charge-state distribution of projectile ions colliding with targets is required in several fields of research such as material science and atomic and nuclear physics but also in accelerator physics, and in particular in regard to the several foreseen large-scale facilities. However, there is a lack of data for collisions in the nonperturbative energy domain and that involve many-electron projectiles. Starting from the etacha model we developed [Rozet, Nucl. Instrum. Methods Phys. Res., Sect. B 107, 67 (1996)10.1016/0168-583X(95)00800-4], we present an extension of its validity domain towards lower velocities and larger distortions. Moreover, the system of rate equations is able to take into account ions with up to 60 orbital states of electrons. The computed data from the different new versions of the etacha code are compared to some test collision systems. The improvements made are clearly illustrated by 28.9MeVu-1Pb56+ ions, and laser-generated carbon ion beams of 0.045 to 0.5MeVu-1, passing through carbon or aluminum targets, respectively. Hence, those new developments can efficiently sustain the experimental programs that are currently in progress on the "next-generation" accelerators or laser facilities.